Przewaga idealizmu w życiu i twórczości Melecjusza Smotryckiego - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2011)
Meletius Smotrytsky’s creative output is almost entirely of a polemical character, since this form and style of scholarly discourse was predominantly used in his times. This method of writing brought him both notoriety and fame. He is to be credited for permanently accommodating the developments of humanistic ideas in the early Baroque period. On the other hand, his changing ideological and religious attitudes, a phenomenon at that time widely regarded as completely natural, led to his recognition as a poet of historical-cultural idealism and religious self-awareness of the Russian people. For Smotrytsky, participation in the life of the Orthodox Church and the Kiev Catholic traditions was the basic principle of scholarly reflection. And owing to his influence this standard also defined the direction of polemical religious conceptions in the first half of the seventeenth century.